Phosphorus uptake in a macrophyte-rich pampean stream - Feijoó, Claudia Silvina (2011)
We estimated phosphate uptake in an eutrophic and macrophyte-rich Pampean stream, in a basin where dominant land use was agricultural activity. Our hypothesis was that phosphate retention may be linked to macrophyte abundance, especially that of submerged plants. Four short-term constant-rate phosphate addition experiments were carried out in late spring, summer, autumn and winter under different discharge, background phosphate concentration and macrophyte abundance. Changes in added soluble reactive phosphorus (SRP) concentration were monitored along the studied reach and corrected for dilution to estimate phosphate uptake length (Sw) and other spiraling metrics (Vf or mass transfer coefficient, and U or nutrient uptake rate). All spiraling metrics indicated a higher SRP retention in spring than in autumn, despite macrophyte cover was similar in both sampling dates (39% and 51%, respectively). Phosphate retention was not detected neither in summer (when macrophyte biomass and especially that of submerged plants was the highest one) nor in winter. Ambient SRP concentrations in the stream were an order of magnitude higher than concentrations observed in pristine streams; nevertheless, under the varying conditions of discharge and phosphate levels observed in our study, we found no retention in summer and winter, a phosphate uptake comparable with those measured in impaired streams in autumn, and with those measured in pristine streams in late spring. © 2010 Elsevier GmbH.